Abstractions for Software- Defined Networks. - CASADO, MARTIN; FOSTER, NATE; GUHA, ARJUN (Communications of the ACM, 2014)
The article reports on the criticality of abstractions in software-defined networks (DSN). It mentions its decoupling of software which controls a network implemented by devices as well as potential in simplifying the expression of algorithms. It notes its role in the development of models based on network programming along with tools for verification. It also points out its provision of packet-processing functions that generalize and evolve network hardware while responding to changes in topology, connections and traffic load shifts.